Působení rtuti na živé organismy - Kenšová, Renáta; Hynek, David; Adam, Vojtěch; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
This study deals with the role of mercury in the environment. It summarizes information about properties of mercury and its species, deals with individual mercury intakes into the environment, anthropogenic or natural, and it follows transport of mercury between individual components of the environment. Part of this thesis is given to the accumulation of mercury and mercury species into organisms. It points out the toxicity of mercury and mercury species, their effect to human organism. In the last chapter there is a resume of the instrumental methods which are commonly used for mercury determination.
Keywords: látky znečišťující životní prostředí; otrava rtutí; Mercury; Mercury Poisoning; Bioaccumulation; rtuť; lidé; bioakumulace; znečištění životního prostředí; Humans; Environmental Pollution; Environmental Pollutants